What’s Past is Prologue: Charleston Conference Proceedings, 2017 (AGAINST THE GRAIN Press, 2018)
Over one hundred presentations from the 37th annual Charleston Library Conference (held November 6–10, 2017) are included in this annual proceedings volume. Major themes of the meeting included data visualization, analysis and assessment of collections and library users, demand-driven acquisition, the future of print collections, and open access publishing. While the Charleston meeting remains a core one for acquisitions librarians in dialog with publishers and vendors, the breadth of coverage of this volume reflects the fact that this conference continues to be one of the major venues for leaders in the publishing and library communities to shape strategy and prepare for the future. Almost 2,000 delegates attended the 2017 meeting, ranging from the staff of small public library systems to the CEOs of major corporations. This fully indexed, copyedited volume provides a rich source for the latest evidence-based research and lessons from practice in a range of information science fields. The contributors are leaders in the library, publishing, and vendor communities.